2016
DOI: 10.1111/disa.12210
|View full text |Cite
|
Sign up to set email alerts
|

Social network characteristics and resource access among formerly displaced households in Lira, Uganda

Abstract: In rural African communities, the support of extended family, friends, and neighbours is essential in borrowing or leveraging land, labour, food, and money, especially at times of social and financial turmoil. Little is known, though, about the nature of the networks and the conditions under which they may generate greater support in post-conflict communities. This study, conducted in the Lira district of northern Uganda, examined the composition, proximity, and size of the networks that households utilise to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…Similarly location provides important information in order to be able to determine the type of social capital households possess (such as bonding, bridging, and linking social capital). It also provides information on whether households differ in quantitative and qualitative terms regarding support originating within and outside the villages [60].…”
Section: International Journal Of Population Researchmentioning
confidence: 99%
“…Similarly location provides important information in order to be able to determine the type of social capital households possess (such as bonding, bridging, and linking social capital). It also provides information on whether households differ in quantitative and qualitative terms regarding support originating within and outside the villages [60].…”
Section: International Journal Of Population Researchmentioning
confidence: 99%
“…This point is consistent with the finding of Bastani (2007) which discovered that education allows people to have relations with people from different contexts and respondents with higher levels of education have larger networks. Obaa and Mazur (2016) also found that there were no meaningful linkages with regard to household heads with no or low level of education.…”
Section: Discussionmentioning
confidence: 88%
“…Social networks are sets of actors linked by social relations or ties (Knoke and Yang, 2008;Kebede and Butterfield, 2009) from which resources may be derived (Obaa and Mazur, 2016). Chai et al (2016) defined social networks as particularistic relationships formed and maintained by interactive and stable kinship, friends, relatives, neighbors or territorial ties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations